Co-morbidities and Hyperinflation Are Independent Risk Factors of All-cause Mortality in Very Severe COPD. (1st August 2014) - Budweiser, Stephan; Harlacher, Martina; Pfeifer, Michael; Jörres, Rudolf A.
Abstract Background: COPD is a multi-component disease that is not sufficiently reflected by FEV1 alone. We studied in patients with very severe COPD, which dimensions of the disease, including co-morbidities, dominate prognosis. Methods: In patients with FEV1 < 30% predicted, anthropometric, laboratory, spirometric and body plethysmographic data, smoking status, alcohol consumption, the level of dyspnoea and exercise performance were assessed. Co-morbidities were categorized by the Charlson-index and the COPD-specific co-morbidity test (COTE). The prognostic value of multiple dimensions was explored using uni- and multivariate survival analyses regarding death from any or respiratory cause. Results: Among 209 patients included (58/151 female/male; FEV1 25.0 (22.0–26.9)%predicted), arterial hypertension (54.1%), hyperlipidemia (38.3%) and diabetes (19.6%) were most common, 57.9% showing a COTE-index of ≥1 point. During follow-up (28 (14–45) months), 121 patients had died, mostly (56.2%) due to respiratory causes. Age, BMI, the ratio of residual volume to total lung capacity (RV/TLC), co-morbidities in terms of the COTE- and Charlson-index, but not FEV1, were significantly associated with all-cause and respiratory mortality. The association of the median values of the Charlson- (HR 1.911 [95%-CI 1.338–2.730]) and COTE-index (HR 1.852 [95%-CI 1.297–2.644], p < 0.001 each) with mortality was similar and stronger when combined with age. In multivariate analyses, only RV/TLC and co-morbidities were independent risk factors of all-cause mortality (p < 0.05 each). Conclusion: In very severe COPD, resting hyperinflation and co-morbidities provide the major prognostic information, whereas the association of the recently introduced COTE-index with mortality was similar to that of the established Charlson-index and even stronger when including age.